Introduction to the special thematic symposium on the ethics of controversial online advertising - Caroline Moraes; Nina Michaelidou (2017)
The field of marketing and consumer ethics has evolved considerably over the past twenty years, yet research on specific areas of advertising ethics remains limited. This limitation persists despite developments in digital technologies, and the impact they have had on advertising practice generally and online advertising more specifically. Online media are becoming increasingly populated by advertising content as consumers continuously navigate ever-evolving mediascapes. Thus, there is a need to examine the ethical issues associated with the use of controversial advertising online, as well as consumers’ responses to such ads. Consequently, this special symposium addresses this literature gap, which is at the intersection of consumer ethics, e-marketing and controversial advertising. The two papers in this special symposium present new research in this area, along with some initial practical recommendations as well as potential for future research.